2023
DOI: 10.3390/ani13121928
|View full text |Cite
|
Sign up to set email alerts
|

Relative Impact of Birth Weight and Early Growth on Neonatal Mortality in Puppies

Abstract: Puppy survival during their first weeks of life can be improved, and early detection of puppies with increased mortality risk is one of the keys to success. In the canine species, the few studies on this subject focused on birth weight, which reflects intrauterine growth. The present work aimed to explore the interconnections between birth weight, early growth and survival until two months of life in the canine species. In total, data from 8550 puppies born in 127 French breeding kennels were analysed. Five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…This evidence, corroborated by the presence of one or few fetuses with low placental efficiency in litters in which the majority of the fetuses showed normal placental efficiency, suggested that the factor responsible for the reduction in the fetal growth is likely fetal or placental rather than maternal. The conclusions of the present study were consistent with the previous finding by Mugnier and co-workers [54], suggesting that a fetal or placental defective function, demonstrated by reduced placental efficiency, impacted the birthweight and the puppy growth rate in the first days of extrauterine life. Thus, placental efficiency based on weight represents a useful and preventive parameter for the evaluation of the neonate in dogs, allowing the identification of puppies that could, in the first weeks of life, be at risk and require more attention and support.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This evidence, corroborated by the presence of one or few fetuses with low placental efficiency in litters in which the majority of the fetuses showed normal placental efficiency, suggested that the factor responsible for the reduction in the fetal growth is likely fetal or placental rather than maternal. The conclusions of the present study were consistent with the previous finding by Mugnier and co-workers [54], suggesting that a fetal or placental defective function, demonstrated by reduced placental efficiency, impacted the birthweight and the puppy growth rate in the first days of extrauterine life. Thus, placental efficiency based on weight represents a useful and preventive parameter for the evaluation of the neonate in dogs, allowing the identification of puppies that could, in the first weeks of life, be at risk and require more attention and support.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in a previous study on the effect of birthweight on neonatal weight growth and risk of mortality in dogs, it was found to be a biphasic effect of the low birthweight condition, with puppies showing a reduced growth rate compared with normal-weight puppies between day 0 and 2, but an increased between day 2 to 7. The same authors reported higher mortality in the low birthweight group between day 0 to 2, with a drastic reduction in the period from day 0 to day 7, detecting significantly higher mortality in low birthweight puppies with low growth rates [54]. Although no data were reported in that study regarding placental evaluation, the data reported in that study found that differences were present in the group of low birthweight puppies and that the combination of low birthweight and low early growth rate should be considered to assess correctly the at-risk puppies.…”
Section: Discussionmentioning
confidence: 83%
“…A single, shared placenta in monochorionic twins is likely to fail to meet the nutritional needs of both foetuses, and intrauterine growth retardation may occur in one or both twins due to imbalances in the placental circulation, especially near the end of pregnancy, when foetal needs increase. Probably, the reduced surface area of the placenta for the foetus leads to placental insufficiency and to the inability to provide adequate foetal nutrients and oxygen [48].…”
Section: Discussionmentioning
confidence: 99%
“…‘Early growth rate after birth is an indicator of wellbeing and has been reported to influence puppy neonatal mortality. Weight loss in puppies has been considered to be a physiological event in the first 48 hours of life, as long as it does not exceed 10 per cent; however, more recently, this has been brought into question (Mugnier and others 2023). Mortality within the first 48 hours after birth is associated with low birth weight and early growth rates of just 4 per cent or under in puppies, due to an increased risk of hypoglycaemia or hypothermia (Mila and others 2015).…”
Section: Neonatal Assessmentmentioning
confidence: 99%
“…Mortality within the first 48 hours after birth is associated with low birth weight and early growth rates of just 4 per cent or under in puppies, due to an increased risk of hypoglycaemia or hypothermia (Mila and others 2015). A large French owner‐based questionnaire study also reported the influence of birth weight and growth rate, when viewed together, on mortality in puppies at several points in the first week of life (Mugnier and others 2023). However, more work is needed in this area to determine optimal growth rates for various breeds particularly during the first 48 hours of life.…”
Section: Neonatal Assessmentmentioning
confidence: 99%